Emerging Disease in Shrimp; Decapod Iridescent Virus 1 Infection - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2021)
Decapod iridescent virus 1 (DIV1) is threatening as emerging pathogen in shrimp industry. The emergence of this pathogen caused serious health impact on both freshwater and marine prawn. Infected giant freshwater shrimp showed alteration of tissue at rostrum surrounding beneath carapace to whitish triangle area and high mortality rate. Typical clinical sign for infected penaeid shrimps was rarely observed. Molecular detection methods for this pathogen were recommended for confirmatory diagnosis. Biosecurity and surveillance program should be considered for preventive strategies of shrimp farm.